Per una poetica della traduzione in Édouard Glissant (TEST Ticontre. Theory Text Translation, 2024)
This paper aims to retrace the thought of Édouard Glissant (Sainte-Marie, 1928 - Paris, 2011) on literary translation, scattered all over his work. Considered by Glissant as a proper art, the translating process is understood as the application of the thought and of the Poetics of Relation. In this sense, translation can be considered as a poetics reflecting the creolizing process fostered by the author. The possibility of dealing with linguistic and cultural diversity, with the distinction between langue and langage, the promotion of multilingualism, the right to opacity and the unpredictability of the target text will be part of this analysis. Questo lavoro ripercorre le tracce delle riflessioni di Édouard Glissant (Sainte-Marie, 1928 - Parigi, 2011) sulla traduzione letteraria, disseminate all’interno della sua opera saggistica. Il processo traduttivo, considerato da Glissant come vera e propria arte, diventa applicazione del pensiero e della Poetica della Relazione. Declinata in questo senso, la traduzione si configura come processo di creolizzazione, altro termine caro all’autore. In virtù della sua capacità di giocare con la diversità, linguistica e culturale, la distinzione tra langue e langage, la promozione del multilinguismo, il diritto all’opacità e l’imprevedibilità nel testo d’arrivo saranno oggetto di questa analisi.